2016
DOI: 10.1103/physrevb.94.144437
|View full text |Cite
|
Sign up to set email alerts
|

Noncollinear antiferromagnetism of coupled spins and pseudospins in the double perovskite La2CuIrO6

Abstract: We report the structural, magnetic and thermodynamic properties of the double perovskite compound La 2 CuIrO 6 from X-ray, neutron diffraction, neutron depolarization, dc magnetization, ac susceptibility, specific heat, muon-spin-relaxation (µSR), electron-spin-resonance (ESR) and nuclear magnetic resonance (NMR) measurements. Below ∼ 113 K, short-range spin-spin correlations occur within the Cu 2+ sublattice. With decreasing temperature, the Ir 4+ sublattice progressively involves in the correlation process. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 59 publications
9
33
3
Order By: Relevance
“…A similar kind of double transition behavior is also observed for La 2 ZnIrO 6 [29]. This is consistent with previous result of P2 1 /n structure [34] but larger than that of P1 ̅ one [35]. Note that the obtained effective magnetic moment μ eff =2.…”
Section: B Magnetic Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar kind of double transition behavior is also observed for La 2 ZnIrO 6 [29]. This is consistent with previous result of P2 1 /n structure [34] but larger than that of P1 ̅ one [35]. Note that the obtained effective magnetic moment μ eff =2.…”
Section: B Magnetic Behaviorsupporting
confidence: 91%
“…6. In earlier reports [34,35], it is found that the magnetization of La 2 CuIrO 6 system with both P1 ̅ and P2 1 /n structures exhibits a small but visible hysteresis loop with the coercivity H C equaling with the framework of short-range FM order. Particularly, a huge coercivity of H C~1 1.96 kOe at 10K is found, which is larger than ∼2.5 kOe, the highest value for hard magnetic ferrites, and is similar to a very recent YMn 0.5 Cr 0.5 O 3 system [44].…”
Section: B Magnetic Behaviormentioning
confidence: 89%
“…(ii) Interestingly, below TN majority of the modes show anomalous softening till 40 K; however below ~ 40 K phonon frequencies become nearly constant. The temperature independent behaviour of phonon frequencies at low temperature (< 40 K ) may be due to the change in magnetic spin-structure and/or emergence of weak Ferromagnetic (FM) ordering as suggested in earlier transport studies [23]. The observed phonon softening below TN is found to be more pronounced for low energy phonon modes S1, S2, S3, S4 and S5 as 0.9, 0.3, 0.4, 0.7 and 0.4 % respectively, while for higher energy phonon modes (i.e.…”
Section: A Raman Scattering and Zone Centre Phonon Calculationsmentioning
confidence: 76%
“…La2CuIrO6 crystallizes in triclinic structure ( 1 P ; space group No. 2) [23]. Within triclinic phase…”
Section: A Raman Scattering and Zone Centre Phonon Calculationsmentioning
confidence: 99%
See 1 more Smart Citation